Fragile equilibriums - Botha, Alta (Michaelis School of Fine Art, 2018)
In my art making I use paper as a primary material. I erode its materiality, perforating the surface in anticipation of whatever may be revealed, searching for new ways of seeing. What emerge are contradictory concepts: reduction and accretion. These mechanisms exist in counterpoise with one another yet the boundaries are blurred – indefinable. The fragile balances that operate within the mechanisms of power are similarly contradictory. It is here that this exploration resides, moving away from what has gone before – as Merleau-Ponty proposes above – taking an ongoing 'route', anticipating the possibility of new developments. papers from industry) and the use of repetition, my concerns are different to those of prominent Minimalist artists. I was first attracted to the visual impact of Minimalist works – and particularly intrigued by Richard Serra's black oil-stick drawings. The extreme reduction of visual and narrative means and a strong emphasis on materiality are central interests. A Minimalist approach to art making allows for reduction of 'noise' and elimination of excess. It pushes me out of my comfort zone of working in mixed media and familiar methodologies. Limitations of media intensify my focus and therefore require me to delve deeper, continuously striving to find and develop new possibilities, leading to new insights and engaging in a process of ongoing incremental unfolding. Fragile equilibriums, operating within complex processes of unconscious and conscious awareness – constantly shifting, adjusting and readjusting. Charcoal is the material that provides a strong link to my childhood place, and establishes a point of reference and departure for the narrative of this study. During my childhood our home was threatened on several occasions by fires in the koppie behind the house. These events were always strangely unifying experiences for our family − we pulled together, as a family, to keep the fires away from our house. Our successful efforts were always accompanied by a sense of achievement and elation, in contrast to the tense undercurrent that existed in our household. Somehow, we performed a balancing act − a fragile equilibrium − between holding something together, and that something falling apart. Throughout my artistic process the challenges remain: How to manipulate and exploit materials, process and formal considerations to say what I want to communicate? How does one give form to traumatic experience? My method in response is 'filtering' − the term offers collectively a concept, structure and process of production. Filtering serves as my concept from which to develop artworks. My choice of materials − charcoal as 'filter' and various kinds of paper used as both surface and support – act as a limit, a controlled framework within which to operate. These self-imposed limitations, to me, symbolically link to the limitations of women in a patriarchal society and the limiting structures and mechanisms of power. Through this body of work, I hope to create a new context and a symbolic 'place' for resistance, setting up new balances for power relations towards fulfilment − unknowing the known − and in the process a reconstitution and a reimagining of the self, embracing the unknown − the possibilities of a new known.